Pengaruh Pemberian Reward Stiker Bintang Terhadap Percaya Diri Anak Kelompok B di TK Thoriqussalam Sidoarjo - Zia Anggraeni Munawaroh (JECED : Journal of Early Childhood Education and Development, 2019)
This research is motivated by the confidence of children in Thoriqussalam kindergarten who have not developed well. This is evidenced by the results of the pretest which shows 11 out of 15 children have not developed their confidence. This study aims to determine the level of confidence of children B before and after it is given assistance in the form of star stickers and to understand the stickers of children B in Thoriqussalam Sidoarjo kindergarten. The method used in this research is quantitative research methods with experimental research models. The form of experiment used is Quasi Experimental with Non Equivalent Control Group Design. From this design, this research is an experimental group that gets help and a control group that doesn't get help. The results obtained are based on the pretest and posttest of the experimental group and the control group. The results of this study are as follows: 1) The initial control of children's confidence before awarding the star stickers has not yet developed in the research or control group, this is evidenced by the results of the pretest that 11 of the 15 experimental group children received an undeveloped score of 1 and 10 out of 15 control children get a value of 1 which means not yet developed. 2) The final condition of self-confidence The child for giving a star prize is very different from the pretest in the experimental group or the control group, this is evidenced by the results of the posttest in the experimental group. 11 out of 15 children get a value of 4 which results in very good development. 3) Giving a star sticker prize agrees to the confidence of the children of Thoriqussalam Sidoarjo Kindergarten B, this is evidenced by Uhitung = 4 and Utabel = 64 with the terms that support Uhitung <Utabel then reject H0 and Ha are approved